2013
DOI: 10.1186/1743-422x-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Systemic distribution of different low pathogenic avian influenza (LPAI) viruses in chicken

Abstract: BackgroundSince we were able to isolate viable virus from brain and lung of H7N1 low pathogenic avian influenza virus (LPAIV) infected chickens, we here examined the distribution of different LPAIV strains in chickens by measuring the viral AI RNA load in multiple organs. Subtypes of H5 (H5N1, H5N2), H7 (H7N1, H7N7) and H9 (H9N2), of chicken (H5N2, H7N1, H7N7, H9N2), or mallard (H5N1) origin were tested. The actual presence of viable virus was evaluated with virus isolation in organs of H7N7 inoculated chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…Several recent reports pointed out that LPAIV may spread systemically in chicken. After intranasal or intratracheal infection with various LPAIV of subtypes H5, H7 and H9 viral RNA was found by RT-PCR in a broad range of tissues beyond the respiratory and gastrointestinal tract and H7N7 virus could be isolated from several tissues (Post et al, 2012(Post et al, , 2013. Thus, one might speculate that systemic, but asymptomatic infection of LPAIV might occur more often than previously anticipated.…”
Section: Discussionmentioning
confidence: 92%
“…Several recent reports pointed out that LPAIV may spread systemically in chicken. After intranasal or intratracheal infection with various LPAIV of subtypes H5, H7 and H9 viral RNA was found by RT-PCR in a broad range of tissues beyond the respiratory and gastrointestinal tract and H7N7 virus could be isolated from several tissues (Post et al, 2012(Post et al, , 2013. Thus, one might speculate that systemic, but asymptomatic infection of LPAIV might occur more often than previously anticipated.…”
Section: Discussionmentioning
confidence: 92%
“…Although studies with (LPAI)H5N1 show that LPAI strains are mostly localized in the lungs in chickens, a recent study showed that systemic distribution of LPAI H7N1, H7N7, H5N2, and H9N2 strains does occur in chickens, with virus detected and isolated in multiple organs, including lung, brain, intestine, peripheral blood mononuclear cells, heart, liver, kidney, and spleen [31, 32]. During 2012, wild birds (sacred Ibis and Egyptian geese) sampled in bird die-offs in Gauteng province tested positive for (LPAI)H7N1 in heart, spleen, and brain samples (Zoonoses Research Unit, University of Pretoria and National Institute for Communicable Diseases, and confirmed by the Onderstepoort Veterinary Institute) (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the systemic detection of LPAIV H5N2, H7N1, H7N7 or H9N2 by real-time reverse transcription PCR (RRT-PCR) in organs and muscles of experimentally infected chickens were also provided but few of these samples (H7N7 LPAIV from samples with a high viral RNA load (Ct ≤ 35 in qPCR) were confirmed by virus isolation (Post et al, 2013). There are reports on the isolation of LPAIV H7N1 in blood of infected turkeys or detection of LPAIV genome in blood, breast and thigh (by RRT-PCR) (Toffan et al, 2008).…”
Section: Assessment Of Lpaiv Transmission Via Raw Poultry Meatmentioning
confidence: 99%